PERBEDAAN PENGARUH PENGGUNAAN CD INTERAKTIF DAN MS.POWERPOINT TERHADAP PRESTASI BELAJAR MEMPERBAIKI SISTEM REM SETELAH DIKENDALIKAN DARI KEMAMPUAN AWAL SISWA (Eksperimen di Sekolah Menengah Kejuruan Muhammadiyah Kabupaten Gunungkidul) - BASUKI, UNTUNG (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
The objective of research was to find out the different effects of learning using interactive Compact Disc (CD) and the one using MS. Power Point media on the learning achievement improving braking system having been controlled from the studentâs prior competency.This study was taken place in SMK Muhammadiyah Karangmojo (Karangmojo Muhammadiyah Vocational Middle School) as treatment group using interactive CD and SMK Muhammadiyah 1 Playen as treatment group using MS.Powerpoint in the XI graders in the school year of 2013-2014. The sample of research was taken using multistage cluster random sampling. This study was an experimental research with covariance analysis (ANACOVA) technique. Technique of collecting data used was test. The instruments used to collect data were physical prior competency and demonstration tests of improving automobile braking system. The physical prior competency test was tested for its validity and reliability to find out the validity and the reliability of the instrument to be used in the research. The physical prior competency test was validated using Micro Computer Adaptive Test (MicroCat) version 3.00 and the reliability of test was examined using Kruder and Richardson (KR-20) formula with r11 = 0.903. Subsequently, the data on physical prior competency and on improving automobile braking system obtained were then examined using prerequisite test including Normality and Homogeneity Tests with correlational regression coefficient. Technique of analyzing data used was a covariance analysis.Considering the result of analysis at significance level (Î± = 0.05), it could be stated that there was a different effects of interactive Compact Disc (CD) and MS. Powerpoint uses on the learning achievement of improving braking system having been controlled from the studentâs prior competency with Fobservation > Ftable (4.997 > 4.00). Using interactive CD media, the learning achievement of the students had the mean value of 80.09 better than that of those using MS.Powerpoint, of 77.28.Â Keywords:Â Â Â Â Â Â Â Â Â  Learning Media, Interactive CD, MS.Powerpoint, Achievement, Student Prior Competency.